TRANSPERITONEAL APPROACH FOR RADICAL NEPHRECTOMY: FIVE YEARS EXPERIENCE AT PAKISTN INSTITUTE OF MEDICAL SCIENCES, ISLAMABAD, PAKISTAN. - Ghaffar, Faisal; Sajid, M. Ali; Anwar, K. (Journal of Ayub Medical College Abbottabad, 2007)
Background: Renal cell carcinoma (RCC) comprises 85% of all renal neoplasms. Radical nephrectomy is the only hope of cure for patients with RCC. Role of chemotherapy and radiotherapy is very limited because of the chemo -radio resistant nature of these tumours. Several surgical approaches have been employed depending upon surgeon preference, size and location of the tumour. Objective of this study is to share the five years experience (from 1999 to 2004) of radical nephrectomy at Urology Department, Pakistan Institute of Medical Sciences (PIMS), that was performed through anterior sub costal trans-peritoneal incision. Methods: It was a descriptive type of study with convenient non probability sampling technique. 100 patients were included. Patients were assessed by their mode of presentation, laboratory investigations, intra-operative findings, control of renal pedicle, total operative time, blood loss, intra-operative and post operative complications. The observations were noted on a proforma and analysed on SPSS version 10. Results: Out of 100 patients, 64% were male and 36% were female with mean age of 58 years. Most common presentation was pain, present in 60% of patients. 88% of patients had normal renal function test. Average tumour size was 7.93cm, diagnosed on ultrasonography (USG) and CT scan. Average time taken to get control of renal pedicle was 73.2minutes. 20% of patients needed venacavatomy and thrombectomy, which was easier through this approach. Mean operative time was 129.44 minutes. Average blood loss was 274.2ml. No intra -operative complications were seen. Mortality rate was 4%. Conclusion: Radical nephrectomy is still the best option for treatment of renal cell carcinoma. There are various surgical approaches, however, anterior subcostal transperitoneal approach is more effective with early control of renal pedicle, less blood loss and minimal manipulation of the kidney thus minimizing the risk of embolism. Keywords: Radical nephrectomy; Anterior subcostal; Transperitoneal.